2021
DOI: 10.3390/ijms22179531
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and IFN-γ Participate in Improving the Immunoregulatory Capacity of Mesenchymal Stem/Stromal Cells: Importance of Cell–Cell Contact and Extracellular Vesicles

Abstract: Mesenchymal stem/stromal cells (MSCs) have an immunoregulatory capacity and have been used in different clinical protocols requiring control of the immune response. However, variable results have been obtained, mainly due to the effect of the microenvironment on the induction, increase, and maintenance of MSC immunoregulatory mechanisms. In addition, the importance of cell–cell contact for MSCs to efficiently modulate the immune response has recently been highlighted. Because these interactions would be diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 188 publications
(380 reference statements)
2
45
0
3
Order By: Relevance
“…It had already been evidenced that the combination of IFNγ and TNFα could change the expression of immunoregulatory molecules in MSCs [34]. Therefore, once the priming conditions were optimized, the next set of experiments was conducted to characterize the phenotype of IFNγ-and TNFα-primed MenSCs (MenSCs*).…”
Section: Discussionmentioning
confidence: 99%
“…It had already been evidenced that the combination of IFNγ and TNFα could change the expression of immunoregulatory molecules in MSCs [34]. Therefore, once the priming conditions were optimized, the next set of experiments was conducted to characterize the phenotype of IFNγ-and TNFα-primed MenSCs (MenSCs*).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse approaches were used in the past to enhance the M2 macrophagemediated healing response by MSC-EVs, most commonly hypoxic pre-conditioning [19,42], inflammatory priming via IFNγ alone [21], or with TNFα+IFNγ [20]. Moreover, it was reported that EVs, particularly from TNFα+IFNγ primed MSC, showed enhanced potential to attenuate inflammation [40,43]. In our study, EVs primed with TNFα+IL1β (MSCp + BCP) were employed, which showed higher levels of TNFα and IL1β (in EV cargo), thereby demonstrating that active soluble cytokines supplied artificially induced MSCs to produce more of the same cytokines, which were at least partly encapsulated within the EV compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of INF-gamma, an increased HLA-ABC expression and induction of the HLA-DR antigen could be observed. Interestingly, it is possible to find reports that activation of MSC cells with the mentioned cytokines and LPS may cause various positive therapeutic effects [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%